Dampak Motivasi Kerja dan Corporate Culture terhadap Kinerja Pegawai PT Bank Jatim Cabang Syariah Kediri - Debryna Suryadhani (Universitas Islam Kadiri, 2020)
The Purpose of this study was to determine the effect of work motivation and corporate culture on employee performance at PT Bank Jatim Syariah Kediri Branch. This research is a quantitative study that show a causal relationship in which sample in this study were 47 employees. Data collection techniques in this study using the questionnaire / questionnaire technique, interview technique and observation techniques. The analysis technique used is descriptive statistical analysis using percentages, averages and standard deviations and for inferential statistical analysis using the multiple linear regression tes, F test, T test, determination coefficient test. The result showed that work motivation was in the good category in term of the indicator motive, hope, incentives, employee oriented. Corporate culture is in the excellent category in terms of employee discipline indicators, timeliness, service group, coordinate, oriented to employees, orient the team, customer oriented. Employee performance is in the good category in terms of the quality of work indicators according to expertise, the quantity of work to reach the target, timelinnes in completing work,employee knowledge, teamwork in completing work. Based on multiple linear regression analysis shows that there is a significant influence between work motivation, corporate culture, and employee performance at PT Bank Jatim Syariah Kediri Branch.